HUBUNGAN LAYANAN PERAWAT DENGAN KEPUASAN PASIEN - SYAHFRIL ARIAWAN HIDAYAT (Media Husada Journal Of Nursing Science, 2023)
Abstract Introduction : Patient satisfaction is one indicator of success of health services. One of the factors which influences patient satisfaction is nurse services. There are five aspects in providing nurse services, namely attention, acceptance, communication, cooperation, and responsibility. Objective : The research objective was to determine the relation between nurse services and patient satisfaction in the Edelweiss room at the Islamic Hospital of Malang, UNISMA. Research methods : This study used the Observational Analytic method with a cross-sectional approach to 52 respondents. Data was collected by using purposive sampling technique from December 2022 to January 2023. The instrument used was a questionnaire sheet and the Statistical test used was Fisher. Results : Based on the results of the study, from 52 respondents there are 47 respondents (90.4%) states that the nurse service was good and satisfied, while no respondents (0%) states that the nurse service was good, but it is not satisfied, and no respondents (0%) who states that the nurse service was not good but satisfied, while those who states that the nurse service was not good and dissatisfied were 5 respondents (9.6%). From the statistical test which was carried out according to the Fisher Exact Test analysis has obtained the value of p = 0.000 <0.05 . Thus H0 is rejected and H1 is accepted, which means there is a relation between nurse services and patient satisfaction in Edelweiss Room of the Malang Islamic Hospital, UNISMA. Suggestion : For this reason, the results of this study should be used as a basic reference for improving the quality of service at the Malang UNISMA Hospital and as an initial lesson for further research.